Narativni pregled literature o vplivu študija medicine na dejavnike življenjskega sloga in zdravje študentov medicine - Kozjek, Ana Karin (Zdravniški vestnik, 2023)
The educational path of medical students is known to be time-consuming and demanding. Coordination of study obligations, extracurricular activities, and own health care can be a great challenge for young people, for which individuals may be differently well equipped. Our narrative review presents an overview of foreign and Slovene literature, summarizing known data on the impact of medical studies on lifestyle factors and health determinants and, thus, onindividual’s physical and mental health. We gathered the literature on these determinants through key-word searches. We found that unbalanced and poorly planned diets, combined with a lack of physical activity, can affect unwanted changes in body composition and increase the chances of developing metabolic disorders and chronic conditions, while a lack of micronutrients can lead to health problems. Studying requirements and chronic stress can adversely affect the sleep and mental state of medical students, with the added influence of a predominantly sedentary lifestyle, which can lead to mental disorders. All this can lead not only to the reduced academic success of students but also to many young people facing health problems early in their challenging careers. So far, there is a lack of systematic research in Slovenia that would allow an assessment of the situation among Slovenian medical students.
Keywords: duševno zdravje; exercise; gibanje; medical students; mental health; nutrition; prehrana; študenti medicine